SPECIFICATION OF POST-COLLATIONAL RESEARCH IN BELARUS - Воропаева, Татьяна (Modern engineering and innovative technologies, 2017)
The article is devoted to the study of the specifics of postcolonial studies in Belarus. The article discusses the problems of the development of postcolonial theory, the emergence of which is due to the most important historical realities of the twentiet